Implementation of Pump Installation Simulation with Smart Relay-Based Water Level for Practical Tools in Learning Process - I Gusti Ngurah Ardana; I Ketut Suherman; I Nyoman Sutarna; I Nengah Darma Susila (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
Polytechnic is a skill-based education with a lot of training and practice, it is necessary to be prepared practicum facilities in terms of instrumentation and control devices, especially pump installation system. An important role in the operation of a system is the electrical system in the form of control, which is useful to facilitate pump installation operation system and this piping is called the Water Level Control. The complicated difficulty is assembling electrical installations manually. This problem can be solved with water level control pump installation system based on smart relay. The aim of this research is to know the discharge of pump water. The data show the average of the water debit calculation theoretically 1.03 liters / minute, meanwhile the average of the debit of test water on tool is 1.44 liter / minute. In conclusion, there is a difference about 0.41 liters / minute, the determination of frictional factor price, coefficient of endurance, pipe diameter, bend type in the specification material not in accordance with the actual material size. It is suggested to the policy makers in the field of vocational education that the tools and practical facilities must be well designed to more effectively consider the condition of student learning.